The Periodic Tile Project: Exploring the Elements With Teacher Candidates Through Science and Art - Allaire, Franklin (Innovations in Science Teacher Education, 2022)
Studies have shown that teacher candidates enrolled in teacher preparation programs, particularly those in early childhood and elementary certification tracks, do not feel comfortable with science content or feel confident in their ability to teach science effectively as they enter student teaching. The Periodic Tile Project is an interdisciplinary project and performance assessment that takes an essential component of the chemistry curriculum that is often treated as a static tool to be memorized and brings the dynamic facets of the elements to life through the integration of science and art. Integrating science and art in performance-based assessments has been shown to increase engagement, self-motivation, and sense of ownership and enhance expression and communication skills in K–12 students. It can provide the same benefits to science teacher candidates. This article describes the use of the Periodic Tile Project with teacher candidates to explore the elements in a fun, meaningful, and memorable way.